Jardin del mar - Bracho, Coral; Suzan, Gerardo (CIDCLI/Consejo Nacional para la Cultura y las Artes, 2000)
Brief poems about what lives in the sea.
Keywords: Children's poetry, Spanish; Poesia infantil espanola; Animales marinos -- Literatura juvenil